Acute exantematic pustulosis generalized acute indicated by meropenem - Coras, Natalia (2019)
We present the case of a 91-year-old female, patient hospitalized for operative wound infection secondary to hip surgery. Antibiotic treatment with meropenem was administered, presenting at 4 days: fever, asthenia and disseminated erythematous rash with non-follicular pustules predominantly of the trunk, extremities and fold areas; In addition, leukocytosis is found with neutrophilia. Histopathological study of skin biopsy showed subcorneal pustules with exocytosis of neutrophils. Antibiotic was discontinued, with clinical improvement 5 days after the suspension of meropenem. There are few reports of cases of acute generalized exanthematous pustulosis caused by meropenem.